Pemanfaatan Ekstrak Lidah Buaya Sebagai Bio-Baterai Untuk Sumber Energi Peralatan Elektronik - Rizal Justian Setiawan; Indra Dwi Suryanto (Jurnal Teknika, 2021)
One of the electrical energy is a battery, but battery will produce waste that is difficult to decompose naturally. The Indonesian government in 2025 wants as much as 23% of national energy to come from renewable energy and 8.3% from bioenergy. The mineral content of aloe vera has the potential as an electrolyte solution, so it can be used to conduct electricity. Based on this, the researchers conducted research by creating an eco-friendly and renewable battery using aloe vera extract. The results of the research are the creation of an aloe vera extract battery box, the voltage generated is 71,5V, the aloe vera extract battery box is capable of turning on LED lights, incandescent lamps and mini electrical control panels. In addition, the use of aloe vera extract as a battery has several advantages such as eco-friendly, rechargeable, cheaper than an ordinary battery and can produces more energy.